Efek Pemberian 2-Metoksietanol Selama Selama Neurulasi Terhadap Menurunnya Kemampuan Kognitif Anak Mencit (Mus Musculus) Swiss Webster Jantan Jantan pada Uji Menggunakan Shuttle Box - Yuanita Windusari (Faculty of Mathtmatics and Natural Sciences, 2003)
The study to investigate the effects of prenatal 2-methoxyethanol (2-ME) exposure , a solvent extensively used in various industries, and is derived from the plastizicer calles dimethoxyethyl phthalate (DMEP), on the learning behaviour and memory of male Swiss Webster mice (Mus musculus) has been conducted. Dams on gestation days 7-10 (group I) or gestation days 14-17 (group II) were injected subcutaneously with 50 and 100 mg/kg body weight (bw) a single dose of 2-ME with a volume of 0.1 ml/10 g bw. Controls were given sterilized bidistilled on gestation days 7-17. The dams were allowed to deliver spotaneously and to rare their offsping, which were ajusted at postnatal day 4, until wearing postnatal day 21. Postweaning bahavior was performed by 9 weeks ols males for learning and memory ability by avoideance learning test using shuttle box. Brains were weighed and fixed in Bouin’s solution untul tough, then the lenght and width of cerebrum were measured, and the razor blade sectioning on the brain was performed to observe were performed to observe the ventricular dilatation for detecting the presence of internal hydrocephaly. The results showed that prenatal 2-ME esposure caused postweaning behavioural deviations in the offsping. The postweaning F1 generation, 2-ME lowered the learning and memory ability showed by the decrease of the avoidance rate in the avoidance learning test. It can be concluded that prenatal 2-ME esposure administered subcutaneously produces behavioural deviations in the postnatal F1 generation of Swiss Webster mice (Mus musculus). The brains weigh and cerebral width decreased.